Psychometric evidence of the generic job satisfaction scale in faculty members of a private Peruvian university - Cordova-Canova, Boris (2025)
Introduction: The Generic Job Satisfaction Scale (GJS) is an accurate psychological instrument; however, it has been used only in few studies in the academic context. Objective: to analyze the GJS’s psychometric evidence in college professors. Method: a total of 338 professors participated. A CFA and convergent analysis were conducted, and factorial reliability and invariance were estimated according to sex, age, and length of service. Results: in both of the analyzed models, a unidimensional structure was confirmed with satisfactory goodness-of-fit indexes; however, at a practical level, the original model was more consistent with the theory. No evidence of invariance was found. Regarding convergent validity, the items showed opposite moderate and strong associations with the Intent to Leave Scale and Organizational Anomie Scale. The reliability values were satisfactory. Discussion: the results suggest that the GJS is a valid and reliable tool for assessing job satisfaction in Peruvian university professors.